Caso de estudio: Análisis y diagnóstico de una empresa del sector agroindustrial peruano, propuesta de un plan estratégico - Rodriguez Blanco, César Miguel (2019)
This research work aims at the strategic analysis of the company Camposol and the agribusiness sector in which it participates, we will see what strategies the company uses to compete in that sector and we will analyze if they are the most convenient according to the opportunities and threats that presents the industry. In the first part of this research work we will make an analysis of the internal and external situation of the company, we will see what are considered to be the key activities that generate value to the company through the analysis of the business model and the value chain; We will see what are the strengths and weaknesses that the company presents and the opportunities and threats that should be seized or fought. In the second part of the work we will analyze the most important matrices to be able to formulate an appropriate strategy for the company, the EFE and IFE matrices serve to measure the strength of the internal position and the success that the company is having with its environment; the SWOT matrix, for the formulation of the strategies to follow and we will also see the mission, vision, policies and strategic objectives that the company has for the future. In the third and fourth part of the work we will present the possible redesigns of the organization chart that will help to implement the previously analyzed strategies and the indicators of objective measurement in order to evaluate if the implementations of the strategies give the expected results.